Camelina sativa L. Oil Mitigates Enteric in vitro Methane Production, Modulates Ruminal Fermentation, and Ruminal Bacterial Diversity in Buffaloes - Ebeid, Hossam M.; Hassan, Faiz-ul; Li, Mengwei; Peng, Lijuan; Peng, Kaiping; Liang, Xin; Yang, Chengjian (Frontiers in Veterinary Science, 2020)
This study was aimed to evaluate the effects of Camelina sativa oil (CO) on fermentation kinetics and methane (CH4) production in rations with different roughage (R) to concentrate (C) ratios. Three total mixed rations (TMRs) were used as substrates (R70:C30, R50:C50, and R30:C70) supplemented with different levels of CO (0, 2, 4, 6, and 8 % on dry matter basis) in an in vitro batch culture system. The enteric CH4 production was determined at different times of incubation while fermentation parameters were measured at the end of incubation. Results revealed that CO significantly decreased (P < 0.05) CH4 production at 48 h in medium (R50:C50) and low (R30:C70) roughage diets than control. Camelina oil at all levels significantly (P < 0.05) affected ammonia nitrogen (NH3-N) and microbial protein (MCP) in all rations. Propionate concentration was increased by supplementing 8% CO to R70:C30 TMR, but it decreased with increasing levels of CO for low and medium roughage diets. Acetate concentration was significantly (P < 0.05) higher at 4% CO supplementation, but it decreased with 8% CO level in R30:C70 TMR. For all rations, CO decreased (P < 0.001) total bacteria, protozoa, and methanogens. Total fungi counts were affected by CO in all rations, especially with a 6 % level in two rations (R30:C70 and R50:C50) and 8 % level with high roughage ration (R70:C30). Supplementation of CO in medium roughage ration (R50:C50) showed a linear (P < 0.05) decrease in bacterial richness and evenness indices along with Shannon diversity as compared to the control. Moreover, CO also increased Firmicutes to Bacteroidetes ratio in all TMRs more effectively at higher levels. Camelina oil also affected the relative abundance of Prevotella in both low and medium roughage diets while increasing the abundance of Ruminobacter and Pseudobutyrivibrio. The present study concluded that CO enhanced fermentation kinetics while decreasing enteric in vitro CH4 production from fibrous diets. Thus, it may be considered as a potentially effective and environmentally friendly way of mitigating CH4 emission from livestock.